TRANSMISSION OF THE PENGUTON DANCE IN KAYUAGUNG: A STUDY OF CULTURAL VALUES AND PRESERVATION STRATEGIES - Eka Endang Lestari; Hartono (RADJA PUBLIKA, 2026)
This research focuses on examining the inheritance of the Penguton Dance in Kayuagung, Ogan Komering Ilir Regency, South Sumatra, focusing more on the cultural values contained and the preservation strategies implemented by the supporting community. The Penguton Dance is the oldest traditional dance in South Sumatra, created in 1889 and is still maintained as the sekapur sirih dance of OKI Regency. This research uses a qualitative approach with ethnographic methods to deeply explore the symbolic meaning, ethnopedagogical values, and cultural inheritance strategies carried out by the Kayuagung community. Data were collected through participatory observation, in-depth interviews with traditional leaders, cultural figures, and the younger generation, as well as documentation studies. The results of the study indicate that the Penguton Dance contains cultural values that include the value of respect for ancestors and distinguished guests, the value of togetherness represented through the involvement of nine clans (Marga Siwe), the value of sacredness and social strata, and aesthetic values reflected in the movements, costumes, and dance properties. The preservation strategies adopted by the community include standardizing the dance as an official regional dance, maintaining the integrity of the nine dancers, staging performances at state events, and regeneration efforts through the involvement of the younger generation. This study concludes that the inheritance of the Penguton Dance requires an integrated approach between preserving cultural values and strategic innovation that adapts to changing times without losing the essence and sacredness of the dance.